Synthesis method and application of super-crosslinked polymer
Porous organic supercrosslinked polymers were synthesized by catalyzing the reaction of 2,7-bis(nitrocarzolyl)-9,9-difluorofluoro or 2,7-bis(nitrocarzolyl)-9,9-dimethylfluoro and dimethoxymethane or 1,4-dimethoxybenzene in an oxygen-free and water-free state, which solved the problem of synthesis of carbon dioxide capture materials and achieved efficient CO2 adsorption effect.
Patent Information
- Application Number
- CN202311309643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-10
AI Technical Summary
How to synthesize porous organic supercrosslinked polymers to solve the problem of the lack of efficient synthesis methods for key materials for carbon dioxide capture and utilization.
Using FeCl3 as an oxidation promoter, 2,7-bis(nitrocarbazolyl)-9,9-difluorofluoro or 2,7-bis(nitrocarbazolyl)-9,9-dimethylfluoro and dimethoxymethane or 1,4-dimethoxybenzene were reacted in an oxygen-free and water-free state, and the supercrosslinked polymer was obtained after quenching, filtration, washing and drying.
A porous polymer containing N and F atoms was successfully synthesized. As an effective CO2 adsorbent, it provides more advanced synthesis strategies and new material ideas, and promotes the advancement of CO2 capture technology.
Smart Images

Figure CN119798655A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hyper-crosslinked polymers, and in particular to a synthesis method and application of a hyper-crosslinked polymer. Background Art
[0002] The oil industry involves the release and generation of carbon dioxide in the process of oil and gas extraction, transportation and energy conversion. The negative impacts of carbon dioxide, including greenhouse effect and acid rain, have a great negative impact on society. Currently, carbon dioxide capture, utilization and storage (CCUS) technology is an important means to solve the greenhouse effect.
[0003] Physical adsorption is an important research aspect of CCUS, and the research on related adsorption materials is mainly focused on porous organic polymers. Currently, it mainly covers metal organic frameworks (MOFs), covalent organic frameworks (COFs), conjugated microporous organics (CMPs), porous organic hyper-crosslinked polymers (HCPs), etc. Among them, the advantage of HCPs over MOFs and COFs is that the synthesis conditions are simple and easy to operate, and the advantage over CMPs is that it has a larger specific surface area, so it is more suitable for gas adsorption.
[0004] Therefore, how to synthesize porous organic hyper-cross-linked polymers has become a technical challenge that needs to be solved at present. Summary of the invention
[0005] The object of the present invention is to provide a method for synthesizing a hyper-crosslinked polymer to solve the above-mentioned problems.
[0006] To achieve the above object, the present invention provides a method for synthesizing a hyper-crosslinked polymer, the method comprising:
[0007] Putting FeCl3 solid into the reactor and keeping the reactor in an oxygen-free and water vapor-free state;
[0008] Adding a mixed solution of a substrate and a reactant into a reactor to perform a first reaction to obtain a first reactant;
[0009] adding methanol to the first reaction product for quenching, and filtering the quenched product to obtain a second product;
[0010] washing and drying the second product to obtain a hyper-crosslinked polymer;
[0011] Wherein, the substrate includes: 2,7-di(nitrogen carbazole)-9,9-difluorofluorene or 2,7-di(nitrogen carbazole)-9,9-dimethylfluorene; the reactant includes: dimethoxymethane or 1,4-dimethoxybenzene.
[0012] The present invention also provides an application of a hyper-crosslinked polymer in CO2 adsorption.
[0013] Technical effects and advantages of the present invention:
[0014] The HCP material containing carbazole-fluorene groups involved in the present invention is a porous polymer containing N and F atoms and is an effective CO2 adsorbent. This patent proposes a synthesis method of this type of material for the first time and applies it to the effective adsorption of CO2. It can provide a more advanced synthesis strategy for the synthesis of this type of porous material, provide new ideas and materials for the capture of CO2, and lead the progress of this research field to a certain extent.
[0015] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a flow chart of a method for synthesizing a hyper-crosslinked polymer;
[0017] Figure 2 This is the infrared characterization image of bis[2,7-di(nitrocarbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP);
[0018] Figure 3 This is the SEM spectrum of bis[2,7-di(nitrocarbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP);
[0019] Figure 4A This is a characterization result diagram of the specific surface area of bis[2,7-di(nitrocarbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP);
[0020] Figure 4B This is a graph showing the pore size distribution characterization results of bis[2,7-di(nitrocarbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP). DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings provided by the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0023] Conjugated microporous organic matter (CMPs, conjucated microporous polymers) can regulate the pore structure from the perspective of molecular design. To achieve large-capacity absorption of CO2, on the one hand, the specific surface area of the material should be increased; on the other hand, the number of electron-rich heteroatoms (such as N, F, etc.) on the skeleton of the polymer material should be increased to promote more stable interactions between CO2 molecules and electron-rich atoms and groups. The HCP material containing carbazole-fluorene groups involved in the present invention is a porous polymer containing N and F atoms and is an effective CO2 adsorbent. This patent proposes a synthesis method for this type of material for the first time and applies it to the effective adsorption of CO2. It can provide more advanced synthesis strategies for the synthesis of this type of porous material, provide new ideas and materials for the capture of CO2, and lead the progress of this research field to a certain extent.
[0024] The following combination Figure 1 The synthesis method of hyper-crosslinked polymers is introduced in detail:
[0025] A method for synthesizing a hyper-crosslinked polymer, the method comprising:
[0026] 1. Place FeCl3 solid into the reactor and keep the reactor in an oxygen-free and water vapor-free state.
[0027] 2. Add the mixed solution of the substrate and the reactant into the reactor to carry out a first reaction to obtain a first reactant.
[0028] The mixed solution is obtained by dissolving the substrate and the reactant in a solvent; wherein the solvent includes one of the following: 1,2-dichloroethane, dichloromethane, and chloroform.
[0029] Wherein, the substrate includes: 2,7-di(nitrogen carbazole)-9,9-difluorofluorene or 2,7-di(nitrogen carbazole)-9,9-dimethylfluorene; the reactant includes: dimethoxymethane or 1,4-dimethoxybenzene.
[0030] The ratio of the mass of FeCl3 to the substrate is in the range of 3:1-6:1; the ratio of the mass of the substrate to the reactant is in the range of 1:1-1:6. The amount of FeCl3 used is large because it is an oxidation promoter, in order to ensure that the substrate reacts fully. The ratio of the substrate to the reactant is between 1 / 1 and 1 / 6 because the substrate is expensive and it is necessary to ensure that it reacts fully.
[0031] 3. Add methanol to the first reaction product for quenching, and filter the quenched product to obtain the second product.
[0032] Wherein, the conditions of the first reaction include: reaction temperature of 80-150° C., reaction time of 24-48 h.
[0033] Among them, methanol can also be ethanol, tetrahydrofuran, ether and other polar solvents containing oxygen atoms, the main purpose of which is to deactivate FeCl3.
[0034] 4. Wash and dry the second product to obtain a hyper-crosslinked polymer.
[0035] The second product is washed and dried to obtain a hyper-crosslinked polymer, including: ultrasonically washing the second product with methanol to obtain a solid after ultrasonication; dispersing the solid after ultrasonication with 60 mL of concentrated hydrochloric acid to obtain a dispersed solution; adding water to the dispersed solution to dilute the concentrated hydrochloric acid to obtain a diluted solid; washing the diluted solid with methanol, and performing Soxhlet extraction on the washed solid with methanol and tetrahydrofuran to obtain an extracted solid; and drying the extracted solid in a vacuum drying oven to obtain a hyper-crosslinked polymer.
[0036] Specifically, the number of ultrasonic washing of the second product with methanol is 3-5 times. The number of washing of the diluted solid with methanol is 3-5 times. The drying conditions include: drying time of 24-48h, drying temperature of 120-150°C.
[0037] Among them, 2,7-di(nitrogen carbazole)-9,9-difluorofluorene + dimethoxymethane, to obtain bis[2,7-di(nitrogen carbazole)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer;
[0038] 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene+1,4-dimethoxybenzene to obtain bis[2,7-di(nitrogen carbazolyl)-9,9-difluorofluorenyl]benzene super cross-linked polymer;
[0039] 2,7-di(nitrogen carbazole)-9,9-dimethylfluorene + dimethoxymethane to obtain bis[2,7-di(nitrogen carbazole)-9,9-dimethylfluorenyl]methane hyper-crosslinked polymer;
[0040] 2,7-Di(nitrocarbazolyl)-9,9-dimethylfluorene+1,4-dimethoxybenzene to obtain bis[2,7-di(nitrocarbazolyl)-9,9-dimethylfluorenyl]benzene super cross-linked polymer.
[0041] The present invention also provides an application of a hyper-crosslinked polymer in CO2 adsorption.
[0042] To better explain the present scheme, examples of hyper-crosslinked polymers synthesized under different conditions are also provided below.
[0043] Example 1
[0044] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (2.256mmol, 171.7mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 80°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Wash the solid with 30mL of methanol ultrasonically for 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 161.2 mg.
[0045] Example 2
[0046] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was evacuated and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (2.256mmol, 171.7mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 140°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 193.0 mg.
[0047] Example 3
[0048] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (2.256mmol, 171.7mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 150°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Wash the solid with 30mL of methanol ultrasonically for 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, 215.2 mg of a reddish brown solid.
[0049] Example 4
[0050] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (2.256mmol, 171.7mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 150°C under nitrogen protection and reflux for 24 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Wash the solid with 30mL of methanol ultrasonically for 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 181.0 mg.
[0051] Example 5
[0052] Add FeCl3 solid (1.128mmol, 183.0mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (2.256mmol, 171.7mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 140°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 172.0 mg.
[0053] Example 6
[0054] Add FeCl3 solid (1.128mmol, 183.0mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (1.128mmol, 85.9mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 140°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 122.0 mg.
[0055] Example 7
[0056] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and 1,4-dimethoxybenzene (2.25mmol, 311.0mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 140°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was extracted with methanol and tetrahydrofuran for 24 hours each, and the solid was dried in a vacuum oven at 120°C for 24 hours to finally obtain the target product bis[2,7-di(nitrogen carbazolyl)-9,9-difluorofluorenyl]
[0057] Benzene hyper-crosslinked polymer, reddish brown solid 161.0 mg.
[0058] Example 8
[0059] Add FeCl3 solid (2.256mmol, 365.9mg) to a 100mL three-necked round-bottom flask. The reaction system was evacuated and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-difluorofluorene (0.376mmol, 200mg) and dimethoxymethane (0.376mmol, 45.9mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 150°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Wash the solid with 30mL of methanol ultrasonically for 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. Then, the solid was Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120° C. for 24 h to finally obtain the target product FFCM-HCP, a reddish brown solid of 162.0 mg.
[0060] Example 9
[0061] Add FeCl3 solid (2.286mmol, 370.6mg) to a 100mL three-necked round-bottom flask. The reaction system was vacuumed and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrocarbazolyl)-9,9-dimethylfluorene (0.381mmol, 200mg) and dimethoxymethane (2.286mmol, 279.1mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 150°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol for 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute the concentrated hydrochloric acid to the system, filter, and wash the solid with 20mL of methanol × 3. The solid was then Soxhlet extracted with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum oven at 120° C. for 24 h to finally obtain bis[2,7-di(nitrocarbazolyl)-9,9-dimethylfluorenyl]methane hypercrosslinked polymer, 224.3 mg of a reddish brown solid.
[0062] Example 10
[0063] Add FeCl3 solid (2.286mmol, 370.6mg) to a 100mL three-necked round-bottom flask. The reaction system was evacuated and nitrogen-filled for three times to ensure that there was no oxygen or water vapor in the reaction flask. Dissolve 2,7-di(nitrogen carbazolyl)-9,9-dimethylfluorene (0.381mmol, 200mg) and 1,4-dimethoxybenzene (2.286mmol, 316.0mg) in 55mL 1,2-dichloroethane and add dropwise to the reaction system with a syringe. After the addition, heat to 150°C under nitrogen protection and reflux for 48 hours. After the reaction is completed, add 30mL of methanol to quench and continue stirring for 1h. Filter the reaction mixture to obtain a brown-black solid. Ultrasonic wash the solid with 30mL of methanol 3 times. Disperse the solid with 60mL of concentrated hydrochloric acid and stir magnetically for 1h. Add water to dilute concentrated hydrochloric acid to the system, filter, and wash the solid with 20 mL of methanol × 3. Then, Soxhlet extraction of the solid was performed with methanol and tetrahydrofuran for 24 h each, and the solid was dried in a vacuum drying oven at 120 ° C for 24 h to finally obtain bis[2,7-di(nitrocarbazolyl)-9,9-dimethylfluorenyl]benzene hypercrosslinked polymer, 236.5 mg of reddish brown solid.
[0064] The present invention also carried out infrared characterization on the bis[2,7-di(nitrogen carbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP) obtained in Example 1, as shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the main absorption peaks are ν3455, 2928, 1639, 1285, 1480, 1112, 1022, 939, 620 cm -1 The broad absorption peak at 3500-3000cm-1 is the CH bond on the aromatic ring, and the peak at 2928cm -1 The absorption peak at 1285 cm represents the methylene group. -1 The absorption peak at 1022cm -1 The absorption peak at corresponds to the -CF2 bond after fluorenyl modification.
[0065] The present invention also carried out SEM testing on the bis[2,7-di(nitrogen carbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP) obtained in Example 1. The SEM spectrum is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the material appears as spherical clusters at the microscopic level, with a particle diameter of less than 200nm and a hole structure interspersed in the middle, indicating that the material can be used for gas adsorption.
[0066] The present invention also characterized the pore structure of the bis[2,7-di(nitrogen carbazolyl)-9,9-difluorofluorenyl]methane hyper-crosslinked polymer (FFCM-HCP) obtained in Example 1, as shown in FIG. Figure 4AThe specific surface area characterization results of FFCM-HCP are as follows: Figure 4B The pore size distribution results are shown in Figure 2. Figure 4A The adsorption and desorption of N2 at 77K indicates that the material has microporous and mesoporous structures, and the BET value is 507m 2 Figure B is a characterization of the pore size distribution of the material, showing that the average pore size of the material is 4.4nm and the pore volume of the micropores is 0.146cm 3 / g.
[0067] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a hyper-crosslinked polymer, characterized in that: The method comprises: Putting FeCl3 solid into the reactor and keeping the reactor in an oxygen-free and water vapor-free state; Adding a mixed solution of a substrate and a reactant into a reactor to perform a first reaction to obtain a first reactant; adding methanol to the first reaction product for quenching, and filtering the quenched product to obtain a second product; washing and drying the second product to obtain a hyper-crosslinked polymer; Wherein, the substrate includes: 2,7-di(nitrogen carbazole)-9,9-difluorofluorene or 2,7-di(nitrogen carbazole)-9,9-dimethylfluorene; the reactant includes: dimethoxymethane or 1,4-dimethoxybenzene.
2. The method according to claim 1, characterized in that The substrate and the reactant are dissolved in a solvent to obtain a mixed solution; wherein the solvent comprises one of the following: 1,2-dichloroethane, dichloromethane, and chloroform.
3. The method according to claim 1, characterized in that The conditions of the first reaction include: reaction temperature range of 80-150° C., reaction time range of 24-48 h.
4. The method according to claim 1, characterized in that: The ratio of the amount of FeCl3 to the amount of the substrate is in the range of 3:1-6:
1.
5. The method according to claim 1, characterized in that The ratio of the amount of the substrate to the amount of the reactant is in the range of 1:1-1:
6.
6. The method according to claim 1, characterized in that The second product is washed and dried to obtain a hyper-crosslinked polymer, comprising: Ultrasonic washing the second product with methanol to obtain an ultrasonically cleaned solid; dispersing the ultrasonicated solid using concentrated hydrochloric acid to obtain a dispersed solution; Adding water to the dispersed solution to dilute the concentrated hydrochloric acid to obtain a diluted solid; Washing the diluted solid with methanol, and performing Soxhlet extraction on the washed solid with methanol and tetrahydrofuran to obtain an extracted solid; The extracted solid is placed in a vacuum drying oven for drying to obtain a hyper-crosslinked polymer.
7. The method according to claim 6, characterized in that The number of times of ultrasonically washing the second product with methanol is 3-5 times.
8. The method according to claim 6, characterized in that The diluted solid is washed with methanol 3-5 times.
9. The method according to claim 6, characterized in that The drying conditions include: drying time of 24-48 hours and drying temperature of 120-150°C.
10. Use of the hyper-crosslinked polymer synthesized according to any one of claims 1 to 9 in CO2 adsorption.
Citation Information
Patent Citations
Porous organic polymer framework material and preparation method and application thereof
CN106496530A
Preparation method of porous super-crosslinked polymer material
CN107759796A
High-performance carbon-based low-pressure carbon dioxide adsorption material as well as preparation method and application thereof
CN114904491A
Spiro-(indane-fluorene) type compounds and their use in organic electronics
WO2023078824A1
Cited By
Preparation method and application of biomass-based super-crosslinked polymer
CN121248963A
Preparation method and application of a biomass-based super-crosslinked polymer
CN121248963B